Hermetia illucens and Poultry by-Product Meals as Alternatives to Plant Protein Sources in Gilthead Seabream (Sparus aurata) Diet: A Multidisciplinary Study on Fish Gut Status - Basilio Randazzo; Matteo Zarantoniello; Gloriana Cardinaletti; Roberto Cerri; Elisabetta Giorgini; Alessia Belloni; Michela Contò; Emilio Tibaldi; Ike Olivotto (Animals, 2021)
The attempt to replace marine-derived ingredients for aquafeed formulation with plant-derived ones has met some limitations due to their negative side effects on many fish species. In this context, finding new, sustainable ingredients able to promote fish welfare is currently under exploration. In the present study, poultry by-products and Hermetia illucens meal were used to replace the vegetable protein fraction in diets totally deprived of fish meal intended for gilthead seabream (Sparus aurata). After a 12-week feeding trial, a multidisciplinary approach including histological, molecular, and spectroscopic techniques was adopted to investigate intestine and liver responses to the different dietary formulations. Regardless of the alternative ingredient used, the reduction in dietary vegetable proteins resulted in a lower incidence of intestine histological alterations and inflammatory responses. In addition, the dietary inclusion of insect meal positively affected the reduction in the molecular inflammatory markers analyzed. Spectroscopic analyses showed that poultry by-product meal improved lipid absorption in the intestine, while insect meal induced increased liver lipid deposition in fish. The results obtained demonstrated that both poultry by-products and H. illucens meal can successfully be used to replace plant-derived ingredients in diets for gilthead seabream, promoting healthy aquaculture.